Creatures of Politics : Media, Message, and the American Presidency - Lempert, Michael; Silverstein, Michael, 1945-2020 (Book collections on Project MUSE., 2012)
It's a common complaint that a presidential candidate's style matters more than substance and that the issues have been eclipsed by mass-media-fueled obsession with a candidate's every slip, gaffe, and peccadillo. This book explores political communication in American presidential politics, focusing on what political insiders call ""message."" Message, Michael Lempert and Michael Silverstein argue, is not simply an individual's positions on the issues but the craft used to fashion the creature the public sees as the candidate. Lempert and Silverstein examine some of the revelatory moments i.